THE APPROPRIATENESS OF ANTITHROMBOTIC THERAPY IN PATIENTS WITH NON-VALVULAR ATRIAL FIBRILLATION IN REAL CLINICAL PRACTICE - A. Y. RYCHKOV; N. Y. KHORKOVA; A. V. MINULINA (Медицинский совет, 2016)
The article evaluates the risk of thromboembolic complications and appropriateness of oral anticoagulants (OAC) in patients with non-valvular atrial fibrillation (AF) upon admission to inpatient treatment at the Tyumen Cardiology Center in 2014. The majority of patients with non- valvular AF, which is 82% of the total number of patients admitted to the hospital, were referred to the high risk group for thromboembolic events (≥ 2 points according to HA2DS2VASc). Before hospitalization, 39.4% of high-risk patients were taking OAC, the majority receiving warfarin. The therapeutic INR range at admission was registered in 30.8% of patients treated with warfarin. 11.1% of high-risk patients received new OAC. Thus, the nticoagulant therapy could be appropriate in 205 patients (19.8% of the high-risk group). There was a relationship between OAC treatment and the risks according to CHADS2 and HAS-BLED, but not CHA2 DS2VASc. OAC were more frequently administered by patients with persistent AF. The article demonstrates the need for a comprehensive educational and organizational initiative aimed at ensuring antithrombotic therapy which corresponds to the current clinical guidelines for patients with non-valvular AF.